Acceleration of hydrogen production during water-olivine-CO2 reactions via high-temperature-facilitated Fe(II) release. (3rd May 2019) - Wang, Jiajie; Watanabe, Noriaki; Okamoto, Atsushi; Nakamura, Kengo; Komai, Takeshi
Abstract: The effects of temperature on hydrogen (H2 ) production in the alteration of olivine [(Mg, Fe)2 SiO4 ] have been investigated under both CO2 -rich (0.5 mol/L NaHCO3 ) and CO2 -free conditions at 225–300 °C. Under CO2 -rich conditions, H2 production rates showed strong temperature dependence, where the rate drastically increased for ≥275 °C, while the rate in CO2 -free conditions was less temperature-dependent. At 300 °C under CO2 -rich conditions, the H2 generation rate was 3 times faster than that under CO2 -free conditions, and a considerable amount of CO2 was simultaneously stored as magnesite [(Mg, Fe)CO3 ]. Increasing the temperature under CO2 -rich conditions promoted olivine consumption, while suppressing both brucite [(Mg, Fe)(OH)2 ] formation and incorporation of Fe(II) into secondary minerals, thus facilitating Fe(II) release and oxidation to produce H2 . It has been revealed for the first time that H2 production during water-olivine-CO2 reactions is markedly accelerated via high-temperature-facilitated Fe(II) release. Highlights: H2 production rate was drastically increased with CO2 mineralization at ≥275 °C. Elevating T in CO2 -rich solution changed both olivine reaction pathway and rate. T influenced Fe(II) partitioning in secondary minerals. A large-scale H2 production with CO2 storage is expected by high-T water-olivine-CO2 reaction.